PENGARUH STRESOR PSIKOLOGIS DAN STRESOR SOSIAL TERHADAP SIKLUS MENSTRUASI - Romauli Romauli; Regina Marintan; Nurul Utami (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2017)
Stress can affect the menstrual cycle because the hormone of stress cortisol hormone which affects the amount of progesterone in the body. The college student of midwifery experience irregular periods at the time before the exam, there is a conflict of interpersonal relationships with friends, and the coursework is accumulate. This study aimed to determine influence of psychological stressors and social stressors of the menstrual cycle midwifery students Dewi Maya Medan from february to march 2016. This was an analytical survey with a cross sectional study design. The sample size was 68 people. Data collection used checklist sheet which contained stress level gauge through the Depression Anxiety Stress Scale (DASS) that have been modified DASS in the form of Linkert scale. We used chi- square test to analysis data. The result shows there was a influence of psychological stressor and menstrual cycle (p=0,014) and there was (p=0.049).